(The level of professional and academic ambition and its relationship to emotional intelligence among outstanding third year secondary students enrolled in private schools for distinguished students in the city of Hama) (Journal of Hama University, 2022)
AbstractThe present study aims at getting familiar with the level of professional and academic ambition and that of emotional intelligence and the identification of the nature of the relationship between the level of professional and academic ambition and emotional intelligence, and the familiarization of the denotation of the difference of the level of professional and academic ambition, and emotional intelligence according to the variant (gender) for third year secondary students at schools for distinguished students in the city of Hama.The researcher used the analytic descriptive method in order to check the aims of this study with its questions and hypothesis and used the measure of the level of professional and academic ambition, and the measure of emotional intelligence. These measures were applied to a sample of fifty-six students between (boys and girls) at the third year of the secondary school for distinguished in the city of Hama. This study reached the following results:-The level of academic and professional ambition for the members of the sample according to these measures and their dimensions was of average degree.-The level of emotional intelligence of the members of the sample was high.-These in no relationship of statistical indication for the level O,OS between the levels of professional and academic ambition and emotional intelligence for the members of the sample study.-There is a variance of statistical indication in the level of professional and academic ambition in accordance with the gender variant. The difference within favour of the male students per overall points and sub-dimensions.-There is no difference of statistical indication in the level O,OS between the averages of the points of the sample study members on the measure of emotional intelligence in accordance with the gender variant. This study concludes with the following set of recommendations:- The creation of an appropriate environment for enhancing the level of ambition for students and intensifying their self-confidence which in turn helps them with a new for the future and achieving the best.-Raising the awareness of families to be aware of the various mechanisms of positive and negative rewarding which can be useful in the enhancement of the level of ambitions in their children.-Conducting studies dealing with constructing and educational guide program for the growing of the level of ambition in the secondary stape school students.-Conducting more studies about the level of ambition, and its relationships to other variants: Agreement, internal and external checking, social upbringing and on other samples.-Conducting more studies about emotional intelligence, and its relationship to other variants like its relationship to scientific thinking, creative thinking, social interaction, adaptation and other samples.-The need to include the courses of study for various specializations in programs for teaching and training distinguished ordinary students as to the skills of emotional intelligence.-Key words: level of professional and academic ambition-emotional intelligence.
Keywords: level of professional and academic ambition-emotional intelligence.